Dog Man : Unleashed - Book 2 - Pilkey, Dav 1966-; Garibaldi, Jose (New York, NY : Graphix, an imprint of Scholastic, 2017)
Dog Man, the newest hero from the creator of Captain Underpants, is still learning a few tricks of the trade. If only the Chief would throw him a bone every once and a while...Dog Man needs to dry up the drool, dust away the dander, and roll out of the refuse if he's going to impress the Chief, and he needs to do it fast! Petey the cat is out of the bag, and his criminal curiosity is taking the city by storm. Can the canine crime biter unleash justice on this ruffian in time to save the city, or will Petey get away with the purrfect crime?
Keywords: Dogs -- Comic books, strips, etc; Police -- Comic books, strips, etc; Comic books, strips, etc -- United States; Dogs -- Fiction; Police -- Fiction; Cartoons and comics; Comic books, strips, etc; Dogs; Police; United States; Comic books, strips, etc; Graphic novels; Humorous comics; Humorous comics; Graphic novels; Comics (Graphic works)